2019
DOI: 10.1002/bab.1854
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐144 relieves chronic constriction injury‐induced neuropathic pain via targeting RASA1

Abstract: MicroRNAs (miRNAs) have been shown to participate in development of neuropathic pain. However, the role of microRNA‐144 (miR‐144) in neuropathic pain remains unclear. In the present study, we established a neuropathic pain mouse model via chronic constriction injury (CCI)‐induction. The successful establishment of this model was confirmed via evaluation of paw withdrawal threshold (PWT) and paw withdrawal latency (PWL). By using this model, we found that miR‐144 was significantly downregulated in CCI‐induced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Nerve injury resulted in neuropathic pain and subsequent pain hypersensitivity. Using the CCI model of neuropathic pain, Zhang et al (2020b) found that mmu-miR-144 was downregulated after inducing CCI. Proinflammatory mediators like Il-6, Il-1β and Tnfα were significantly elevated after CCI induction.…”
Section: Downregulated Micrornas In Neuropathic Pain Human Micrornas ...mentioning
confidence: 99%
“…Nerve injury resulted in neuropathic pain and subsequent pain hypersensitivity. Using the CCI model of neuropathic pain, Zhang et al (2020b) found that mmu-miR-144 was downregulated after inducing CCI. Proinflammatory mediators like Il-6, Il-1β and Tnfα were significantly elevated after CCI induction.…”
Section: Downregulated Micrornas In Neuropathic Pain Human Micrornas ...mentioning
confidence: 99%
“…Neuropathic pain (NP) is a chronic pain, and it is a disease caused by somatosensory nervous system dysfunction or a variety of factors, including metabolic disorders, inflammation, and surgical trauma [1, 2]. At present, NP has become a major public health problem faced by all countries in the world.…”
Section: Introductionmentioning
confidence: 99%
“…CCI downregulated miR‐140 and miR‐144 expression in the DRG. Intrathecally injected miR‐140 and miR‐144 agomir decreased inflammatory factor secretion and ameliorated hyperalgesia by targeting sphingosine‐1‐phosphate receptor 1 (S1PR1) and RAS P21 protein activator 1 (RASA1), respectively 43,44 …”
Section: Studying Mirna Neuropathic Pain Mechanismsmentioning
confidence: 99%